Composite UHDRS Correlates With Progression of Imaging Biomarkers in Huntington's Disease. Issue 5 (20th January 2021) - Estevez‐Fraga, Carlos; Scahill, Rachael I.; Durr, Alexandra; Leavitt, Blair R.; Roos, Raymund A.C.; Langbehn, Douglas R.; Rees, Geraint; Gregory, Sarah; Tabrizi, Sarah J.
Abstract: Background: The composite Unified Huntington's Disease Rating Scale (cUHDRS) is a multidimensional measure of progression in Huntington's disease (HD) being used as a primary outcome in clinical trials investigating potentially disease‐modifying huntingtin‐lowering therapies. Objective: Evaluating volumetric and structural connectivity correlates of the cUHDRS. Methods: One hundred and nineteen premanifest and 119 early‐HD participants were included. Gray and white matter (WM) volumes were correlated with cUHDRS cross‐sectionally and longitudinally using voxel‐based morphometry. Correlations between baseline fractional anisotropy (FA); mean, radial, and axial diffusivity; and baseline cUHDRS were examined using tract‐based spatial statistics. Results: Worse performance in the cUHDRS over time correlated with longitudinal volume decreases in the occipito‐parietal cortex and centrum semiovale, whereas lower baseline scores correlated with decreased volume in the basal ganglia and surrounding WM. Lower cUHDRS scores were also associated with reduced FA and increased diffusivity at baseline. Conclusion: The cUHDRS correlates with imaging biomarkers and tracks atrophy progression in HD supporting its biological relevance. © 2021 International Parkinson and Movement Disorder Society